ChemInform Abstract: Iron Carbide Nanoparticles Encapsulated in Mesoporous Fe‐N‐Doped Carbon Nanofibers for Efficient Electrocatalysis. Issue 37 (September 2015) - Wu, Zhen‐Yu; Xu, Xing‐Xing; Hu, Bi‐Cheng; Liang, Hai‐Wei; Lin, Yue; Chen, Li‐Feng; Yu, Shu‐Hong
Abstract A new catalyst for the oxygen reduction reaction in fuel cells and metal—air batteries is prepared from aqueous solutions of carbonaceous nanofibers, pyrrole, and FeCl3 (room temperature, 4 h, followed by pyrolysis under flowing N2).